2010
DOI: 10.4049/jimmunol.0903961
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Regulatory T Cells in Th17-Mediated Minor Antigen-Disparate Rejection

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 53 publications
(53 reference statements)
4
43
0
1
Order By: Relevance
“…However, there is a certain degree of plasticity that Tregs retain, and under specific conditions they may adopt a proinflammatory phenotype (32). This phenotype includes a helper-like role and has been observed in different models, including vaccination (33), tumors (34), or graft rejection (35). In particular, Addey et al (34) demonstrated that, in the murine urothelial carcinoma model, Tregs upregulated genes characteristic for a Th cell phenotype, such as proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a certain degree of plasticity that Tregs retain, and under specific conditions they may adopt a proinflammatory phenotype (32). This phenotype includes a helper-like role and has been observed in different models, including vaccination (33), tumors (34), or graft rejection (35). In particular, Addey et al (34) demonstrated that, in the murine urothelial carcinoma model, Tregs upregulated genes characteristic for a Th cell phenotype, such as proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 was reported to promote the maturation of dendritic cell progenitors (29) and graft inflammation (30) in separate models of murine cardiac allograft rejection, thus suggesting its potential role in facilitating the acute rejection response. Increased expression of IL-17 mRNA and protein has been demonstrated during the early stages of renal allograft rejection in both humans (31,32) and animal models (33,34). Despite circumstantial evidence implicating a role for IL-17 in the early phases of renal allograft rejection, the role of IL-17 deficiency has not been previously examined in an animal model of renal allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…+ T cells, which do not express cytokines, might be important for the risk of graft-versus-host disease after bone marrow transplantation [37][38][39], but probably have little impact on the risk for acute rejection after kidney transplantation [40]. Currently, we are investigating how alloreactive CD137 + T cells develop following kidney transplantation, and whether or not the presence of certain subsets of alloreactive T cells are related specifically to the risk for acute rejection after kidney transplantation.…”
Section: Cd4mentioning
confidence: 99%